The Circular Polarization of Sagittarius A at Submillimeter Wavelengths - Muñoz, D. J; Marrone, D. P; Moran, J. M; Rao, R (The Astrophysical journal, 2012)
We report the first detections of circularly polarized emission at submillimeter wavelengths from the compact radio source and supermassive black hole candidate Sgr A* at a level of 1.2% + or - 0.3% at 1.3 mm wavelength (230 GHz) and 1.6% + or - 0.3% at 860 mu m (345 GHz) with the same handedness, left circular polarization (LCP), as observed at all lower frequencies (1.4-15 GHz). The observations, taken with the Submillimeter Array in multiple epochs, also show simultaneous linear polarization (LP) at both wavelengths of about 6%. These properties differ sharply from those at wavelengths longer than 1 cm (frequencies below 30 GHz), where weak circular polarization (CP) (~0.5%) dominates over LP, which is not detected at similar fractional limits. We describe an extensive set of tests to ensure the accuracy of our measurements. We find no CP in any other source, including the bright quasar 1924-292, which traces the same path on the sky as Sgr A* and therefore should be subject to identical systematic errors originating in the instrument frame. Since a relativistic synchrotron plasma is expected to produce little CP, the observed CP is probably generated close to the event horizon by the Faraday conversion process. We use a simple approximation to show that the phase shift associated with Faraday conversion can be nearly independent of frequency, a sufficient condition to make the handedness of CP independent of frequency. Because the size of the [tau] = 1 surface changes by more than an order of magnitude between 1.4 and 345 GHz, the magnetic field must be coherent over such scales to consistently produce LCP. To improve our understanding of the environment of SgrA* critical future measurements includes determining whether the Faraday rotation deviates from a [lambda] super(2) dependence in wavelength and whether the circular and linear components of the flux density are correlated.